Implementasi Algoritma Simon Pada Aplikasi Kamus Perubahan Fi’il (Kata Kerja Bahasa Arab) Berbasis Android - Rahmad Akbar; Bambang Pramono; Rizal Adi Saputra (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2021)
Keywords — String Matching Algorithm, Simon Algorithm, Android Fi'il Changes Dictionary Shorof science or Tashrif is the scientific field of word derivation in Arabic, one focus of the discussion in this field is the process of changing verbs or also known as Fi'il into several other types of words, such as Fi'il Mudhori ', Fi'il Madhi , Fi'il Amr, Fi'il Nahi, Isim Fa'il, Isim Maf'ul, Isim Zaman, Isim Makan, Isim Alat, Masdar or Masdar mim. The process of learning Shorof science is still mostly carried out in traditional ways, especially in the pesantren environment by memorizing the derivatives of these words and their translations. While one of the basic books that is often used is the book Amtsilah At-Tashrifiyah written by KH.Ma'shum bin Ali as a reference for the process of changing words, while looking for a translation in Indonesian must use an Arabic-Indonesian dictionary. This study aims to simplify the word search process by making an android-based dictionary of Fi'il change and utilizing the Simon Algorithm as a word search method, so as to simplify the learning process of Shorof's knowledge. Simon's algorithm is a string matching algorithm where the matching phase is carried out from left to right by initializing each index on a given pattern. After testing, the word search process can be carried out with an average running time of 3.67097786 milli second for searching Indonesian words and 23.8447333 milli second for searching Arabic words.